2015
DOI: 10.1007/s00894-015-2835-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling studies demonstrate key mutations that could affect the ligand recognition by influenza AH1N1 neuraminidase

Abstract: The goal of this study was to identify neuraminidase (NA) residue mutants from human influenza AH1N1 using sequences from 1918 to 2012. Multiple alignment studies of complete NA sequences (5732) were performed. Subsequently, the crystallographic structure of the 1918 influenza (PDB ID: 3BEQ-A) was used as a wild-type structure and three-dimensional (3-D) template for homology modeling of the mutated selected NA sequences. The 3-D mutated NAs were refined using molecular dynamics (MD) simulations (50 ns). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, NA V263I has not been studied in an H3N2 background yet. However, a comprehensive study of NA V263I involvement at the structural level suggested the isoleucine, which is two methyl groups higher than a valine, could allow important changes by altering hindrance effects [37]. It was also suggested that this site was part of an epitope that was suitable for therapeutic monoclonal antibodies, and that an amino acid change at this position modified the immune response [38].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, NA V263I has not been studied in an H3N2 background yet. However, a comprehensive study of NA V263I involvement at the structural level suggested the isoleucine, which is two methyl groups higher than a valine, could allow important changes by altering hindrance effects [37]. It was also suggested that this site was part of an epitope that was suitable for therapeutic monoclonal antibodies, and that an amino acid change at this position modified the immune response [38].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations located at the binding site can affect the structural and/or functional behaviour of the protein. However, mutations located outside the binding site could possibly alter the structure of the binding pocket and, thus, could be associated with drug resistance (Ramírez-Salinas et al, 2015). Kar & Knecht (2012) suggested that the binding pockets of the mutated N8 NAs were less flexible as compared with the binding pocket of the WT protein.…”
Section: Discussionmentioning
confidence: 99%